Low-Density Lipoprotein Cholesterol, Apolipoprotein B, and Risk of Coronary Heart Disease: From Familial Hyperlipidemia to Genomics. (July 2013) - Imes, Christopher C.; Austin, Melissa A.
Coronary heart disease (CHD) affects 17 million people in the United States and accounts for over a million hospital stays each year. Technological advances, especially in genetics and genomics, have changed our understanding of the risk factors for developing CHD. The purpose of this article is to review low-density lipoprotein cholesterol (LDL-C), apolipoprotein B (apo B), and risk of CHD. The article focuses on five topics: (1) a description of lipoprotein classes, normal lipoprotein metabolism, and the biological mechanism of atherosclerosis; (2) a review of selected epidemiologic and clinical trial studies examining the associations between elevated LDL-C and apo B with CHD; (3) a brief review of the familial forms of hyperlipidemia; (4) a description of variants in genes that have been associated with higher LDL-C levels in candidate gene studies and genome-wide association studies (GWAS); and (5) nursing implications, including a discussion on how genetic tests are evaluated and the current clinical utility and validity of genetic tests for CHD.